Fibroblast Growth Factor 10 and Vertebrate Limb Development - Jin, Libo; Wu, Jin; Bellusci, Saverio; Zhang, Jin-San (Frontiers in Genetics, 2019)
Early limb development requires fibroblast growth factor (Fgf)-mediated coordination between growth and patterning to ensure the proper formation of a functional organ. The apical ectodermal ridge (AER) is a domain of thickened epithelium located at the distal edge of the limb bud that coordinates outgrowth along the proximodistal axis. Considerable amount of work has been done to elucidate the cellular and molecular mechanisms underlying induction, maintenance and regression of the AER. Fgf10, a paracrine Fgf that elicits its biological responses by activating the fibroblast growth factor receptor 2b (Fgfr2b), is crucial for governing proximal distal outgrowth as well as patterning and acts upstream of the known AER marker Fgf8. A transgenic mouse line allowing doxycycline-based inducible and ubiquitous expression of a soluble form of Fgfr2b has been extensively used to identify the role of Fgfr2b ligands at different time points during development. Overexpression of soluble Fgfr2b (sFgfr2b) post-AER induction leads to irreversible loss of cellular -catenin organization and decreased Fgf8 expression in the AER. A similar approach has been carried out pre-AER induction. The observed limb phenotype is similar to the severe proximal truncations observed in human babies exposed to thalidomide, which has been proposed to block the Fgf10-AER-Fgf8 feedback loop. Novel insights on the role of Fgf10 signaling in limb formation pre- and post-AER induction are summarized in this review and will be integrated with possible future investigations on the role of Fgf10 throughout limb development.